Constructing China's Roads as Works of Art: A Case Study of "Esthetic Greenway" Construction in the Shennongjia Region of China. (21st March 2013) - Cheng, B.; Lv, Y.; Zhan, Y.; Su, D.; Cao, S.
Abstract Sustainable development based on economic growth that is environmentally sound is increasingly essential. To achieve both ecological and social progress without detracting from China's primary economic objectives, China's Ministry of Communications has promoted the strategy of harmonious road systems, for which artistic principles are incorporated in the road's design to balance the needs of the environment with those of socioeconomic development without neglecting human esthetic needs. To illustrate the new strategy's impact, we examined a project that has been conducted following this approach in the Shennongjia region of China's Hubei Province since 2004. As in the use of ecological corridors, the new strategy emphasizes the need to decrease the impact of road construction on plant and animal habitats by emphasizing the protection of existing natural habitats and the use of local species for revegetation of the land surrounding the roads. However, it also emphasizes the need to improve traffic safety, promote local tourism and economic growth, and provide a demonstration to citizens (including bureaucrats) of the need for environmental protection both during and after road construction. After 6 years of monitoring, we found that the new strategy both satisfies the human desire for beauty and improves the road's harmony with nature and the surrounding visual landscape while promoting environmental conservation, ecotourism, traffic safety, socioeconomic development, and cultural values. This approach will help to guide future landscape design, planning, and management. Copyright © 2013 John Wiley & Sons, Ltd.